Deep-brain stimulation for dystonia: current indications and future orientations. (January 2014) - Thobois, Stéphane; Danaila, Teodor; Polo, Gustavo; Simon, Emile; Mertens, Patrick; Broussolle, Emmanuel
ABSTRACT: Deep-brain stimulation of the internal globus pallidus is a therapeutic option for dystonia. However, the available data are heterogeneous, ranging from single case reports to a few controlled studies. The outcomes are also largely heterogeneous, depending mostly on the etiology of the dystonia. Except for some well-established good indications, such as primary generalized dystonia and tardive dyskinesia, the efficacy of globus pallidus stimulation remains debated for several forms of dystonia. In addition, many issues are still unsolved, such as the best target of stimulation and the interest of simultaneously combining multiple targets of stimulation or not. Finally the efficacy of new strategies of treatment, such as cortical stimulation, remains to be determined. The aim of this review is to cover these different aspects and give an overview of the current indications and future orientations.